Branding at Mewar Rugs - Sinha, Ritu (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2013)
The case discusses about the Company, Mewar Rugs known for high quality hand woven rugs exporting majority of the US and the rest of the world.The unique selling proposition (USP) of the company is hand woven carpets which depend upon the creative designs and workmanship of the weavers.There is huge demand for their finished products in developed countries and are primarily supplying their finished products to the exclusive showrooms and outlets of premium luxury home decors.They have tied up with some leading designers that are helping them to build their brand on the concept of co-branding.The process of manufacturing is highly labor intensive where the majority of the processes is done by the weavers manually.The company is investing a huge amount of resources in the process and infrastructure.The company is also doing well on sales front but lacks innovative approaches of marketing.This may endanger the competitive advantages of the handwoven carpet in coming time at global arena. This case is an att empt to discuss whether Mewar Rugs needs a new brand identity and how its image is signifi cantly important for this kind of product where demand exceeds the supply